Efficacy of monoterpenes against the cowpea weevil, callosobruchus maculatus f. (coleoptera: bruchidae), in stored cowpea seeds - Abdelgaleil, Samir A.; Mohamed, Magdy I.; Kassem, Shihata M.; El-arami, Sailan A. (2010)
In the present study the contact and fumigant toxicities of seven monoterpenes namely, (R)-carvone, 1-8-cineole. cuminaldehyde, (S)-tenchone, geraniol, (S)-Hmonene and (R)-linalool, were evaluated against the adults of Callosobruchus macuatus F. The potential of the most effective monoterpencs for control the insect in stored cowpea seeds was also examined. The tested monoterpenes showed potent contact toxicity against the adults of C. maculatus within 24 h of exposure.
Includes references.
Summary in Arabic.
1
Keywords: Cowpea weevil -- Control; Cowpea -- Diseases and pests -- Control; Monoterpenes